Tradisi Melempar Bunga Ala Barat: Analisis Terhadap Simbol Harapan dan Keberuntungan dalam Upacara Perkawinan di Desa Pekubuan Tanjung Pura - Adelia Riana (ALADALAH: Jurnal Politik, Sosial, Hukum dan Humaniora, 2025)
The tradition of marriage is an important part of society's culture that often symbolizes hope and good fortune for the newlyweds and their guests. One of the traditions that has developed recently is the tradition of throwing a bouquet. This study examines the tradition of throwing a bouquet in wedding ceremonies in Pekubuan Village, Tanjung Pura District, Langkat Regency. Originating from Western culture, this tradition has become part of modern wedding ceremonies in the village. The research aims to understand the perspectives of the community and Islamic law regarding this tradition, particularly concerning the symbolism of hope and good fortune.A qualitative research method with a normative-theological and juridical approach was employed. Data was collected through in-depth interviews, observations, and document studies. The results indicate that local people view this tradition as entertainment without serious belief. However, local scholars have differing opinions; some reject it as contrary to Islamic law due to its elements of tasyabbuh (imitation) and khurafat (superstitions), while others consider it acceptable as long as it does not involve beliefs that contradict the principles of tawhid.This research is expected to provide new insights into the tradition of throwing a bouquet and to open up further discussions on the influence of modernization on Islamic values in local traditions. Thus, it is hoped that society can be more discerning in addressing evolving traditions while considering religious values and maintaining a balance between cultural heritage and contemporary demands.